Cd, Cu and Pb Concentration Levels in Horseshoe Crab Nesting Grounds of Pahang Coast, Malaysia - Kassim, Zaleha; Yunus, Kamaruzzaman; Akbar, John; M. C., Ong (Asian Network for Scientific Information, 2010)
Balok, Pekan and Penor have been observed to be nesting grounds of the horseshoe crab. Present study was conducted to assess the metal concentration in sediment of horseshoe crab the nesting ground along the east coast of peninsular Malaysia. Acid Digestion was performed using (HF, HNO3, HCl, EDTA and H3BO4) before determining the actual concentration of heavy metals using ICPMS. 2-way ANOVA was used to determine the significance of the results. In all stations, Pb was in highest concentration (40.36 μg g-1) followed by Cu (13.44 μg g-1) and the least concentrated metal in the nesting ground was Cd with the high concentration of (0.26 μg g-1). EF values showed that Pb is of anthropogenic source and Cd is of minimum enrichment. Although the levels of Pb are low and regarded harmless to the horseshoe crab, the fear of it affecting those who consume the eggs as well as the crab is still in consideration.